MEMBANGUN CITRA GLOBAL DARI AKAR LOKAL: PENDEKATAN REBRANDING INOVATIF BAGI UMKM DESA SERUT, KABUPATEN JEMBER DALAM KONTEKS GLOKALISASI - Aprillianto , Bayu; Sulistyo, Agung Budi; Maharani, Bunga; Wulandari, Gusti Ayu; Miqdad, Muhammad; Wulandari, Novi; Mas’ud, Imam (Universitas Mataram, 2024)
Serut Village, located in Panti Subdistrict, Jember Regency, is home to numerous highly potential Micro, Small, and Medium Enterprises (MSMEs), including wood and bamboo crafts, stone crafts, aluminum works, mushroom cultivation, various local snacks, and palm sugar products. The primary issues faced by these MSME actors are weak business identity and lack of product branding. The distribution of products is conducted through middlemen, causing MSME products to be sold under the middlemen's brand rather than their own. The method of the activities were carried out through: 1) Focus Group Discussions (FGD) with MSME actors and village officials, 2) observations and documentation, 3) Compiling MSME business profiles through the creation of logos and profile videos. The objective are to rebrand MSMEs by focusing on aspects of local wisdom to build the identity of Serut Village MSMEs, enhance product competitiveness, and expand the distribution chain towards the global market. The results of the activities resulted in the mentoring of six MSMEs engaged in wood and bamboo crafts, stone crafts, aluminum works, mushroom cultivation, various local snacks, and palm sugar products. The business profile compilation yielded six MSME logos and profile videos, crafted based on local character and wisdom, thereby strengthening MSME branding in the global market. Hence, the conclusion is MSME actors have not yet understood the importance of product branding. The mentoring results provided MSME actors with the opportunity to market their products with their own branding.